2019
DOI: 10.1038/s41598-019-45956-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body mass index, waist circumference, waist-to-height ratio, and high blood pressure among adolescents: a cross-sectional study

Abstract: The purpose of the present study was to examine the associations between body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), and high blood pressure (HBP), and to determine which anthropometric parameters can best predict HBP among Lithuanian adolescents aged 12–15 years. Data from the survey of “Prevalence and Risk Factors of HBP in 12–15-Year-Old Lithuanian Children and Adolescents (Study 1, 2010–2012)” were used; a total of 7,457 respondents (3,494 boys and 3,963 girls) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 64 publications
9
36
2
5
Order By: Relevance
“…The prevalence of high blood pressure among adolescents is increasing [3]. In our study, the prevalence of elevated BP was compatible with recent reports which grouped pre-hypertensive and hypertensive status in the analysis [25,26]; and also with the total population of ERICA study, in which 14.5% pre-hypertensive and 9.6% hypertensive adolescents were identified, aiming total prevalence of elevated BP of 24.1% [14]. Despite that, it is a not common practice to screen for hypertension among children and adolescents routinely [27].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of high blood pressure among adolescents is increasing [3]. In our study, the prevalence of elevated BP was compatible with recent reports which grouped pre-hypertensive and hypertensive status in the analysis [25,26]; and also with the total population of ERICA study, in which 14.5% pre-hypertensive and 9.6% hypertensive adolescents were identified, aiming total prevalence of elevated BP of 24.1% [14]. Despite that, it is a not common practice to screen for hypertension among children and adolescents routinely [27].…”
Section: Discussionsupporting
confidence: 92%
“…As indicated on the findings of the current study, among other anthropometric body composition variables, BMI and height were consistently significantly associated with SBP in correlation, linear regression and logistic regression. A study by Kuciene and Dulskiene [20] reported that body mass and stature in boys and body mass in girls were the most influential predictors of SBP. Furthermore, it was observed that age and body size in boys accounted for most of the SBP differences than percentage body fat [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…All models developed in this study use Body Mass Index (BMI) and Abdominal Circumference (AC) values for the calculations, since both are strongly associated with hypertension and its risk factors [41]- [44].…”
Section: Methodsmentioning
confidence: 99%